Take-off performance of a single engine battery-electric aeroplane - Gratton, Guy; Delaney, Thomas; Zaghari, Bahareh; Kendall, Gary (Cambridge University Press (CUP), 2024)
This paper investigates the take-off performance of a single engine battery-electric aeroplane, using the example of the 300kg Sherwood eKub. It shows analysis of take-off performance of such an aeroplane must include as a minimum two new parameters not normally considered: time at full throttle and state of charge. It was shown in both ground and flight test that the state of available power reduces both as the throttle is fully open, and as battery charge is consumed, although recovers partially when power is reduced for a period. It is possible to schedule take-off performance as a function of the usual parameters plus state of charge. Because of the reducing climb performance with use of state of charge, and the requirement in airworthiness standards for minimum climb performance being available, it becomes necessary to introduce the concept of minimum-indicated state of charge for take-off, SoCiMTO; means to calculate that are shown for compliance with both microlight aeroplane standards and larger aeroplane standards, and the calculations are demonstrated for the eKub. Conclusions are also drawn about the use of commercial products SkyDemon and Google Earth for recording and analysing aeroplane performance data.
Keywords: Electric Flight; Take-off; Aircraft certification; Aeroplane performance; CS-23; 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; Aerospace & Aeronautics; 35 Commerce, management, tourism and services